Perception of the quality of life in work througout the Physical education teaching career - Jorge Both; Juarez Vieira do Nascimento; Adriano Ferreti Borgatto (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n4p372   The objective of this study was to analyze the association between Quality of Life in the Teaching Profession (QVTD) and Professional Development Cycles (CDP) among Physical Education teachers working for the Santa Catarina state education department. The sample was made up of 580 teachers from different parts of the state, 265 of whom were male and 315 of whom were female. Data collection was carried out using the QVT-PEF to assess QVTD and years in the teaching profession to determine CDP. Multinomial logistic regression analysis was employed to determine prevalence ratios and the likelihood ratio test was used to determine whether associations were significant (p<0.05). Both statistical procedures were carried out using SPSS version 11.0. The results demonstrated that the teachers' lowest levels of satisfaction were in the dimensions "Adequate and fair compensation", "Safe and healthy work conditions", "Social integration in the work organization" and "Work and total life space". A strong association between some of the QVTD dimensions and CDP revealed that, as the years passed, teachers tend to become less satisfied with working autonomy, and salaries and working conditions, all of which may have had an influence on the final QVTD score.